Genetic structure of East Antarctic populations of the moss Ceratodon purpureus - Laurence Clarke; Ayre, DJ; Robinson, SA (2009)
The capacity of the polar flora to adapt is of increasing concern given current and predicted environmental change in these regions. Previous genetic studies of Antarctic mosses have been of limited value due to a lack of variation in the markers or non-specificity of the methods used. We examined the power of five microsatellite loci developed for the cosmopolitan moss Ceratodon purpureus to detect genetically distinct clones and infer the distribution of clones within and among populations from the Windmill Islands, East Antarctica. Our microsatellite data suggest that the extraordinarily high levels of variation reported in RAPD studies were artificially elevated by the presence of contaminants. We found surprisingly little contribution of asexual reproduction to the genetic structure of the Windmill Islands populations, but more loci are required to determine the distribution of individual clones within and among populations. It is apparent that Antarctic populations of C. purpureus possess less genetic diversity than temperate populations, and thus have less capacity for adaptive change in response to environmental variation, but more markers are needed to resolve the total genetic diversity in Antarctic C. purpureus and other mosses.